Qualidade da madeira de Tectona grandis L. f. produzida em sistema silvipastoril e em monocultura - Souza, Leandro Vinicius Carbonato de (2024)
This study aimed to assess the quality of Tectona grandis L. f. wood produced in a silvopastoral system and monocultures aged 13 years located in different municipalities in the state of Mato Grosso, Brazil. The first chapter evaluated the quality of teak wood from three clones (TG1, TG2, and TG3) and seminal material in a silvopastoral system in the Alta Floresta municipality, MT. We assessed the morphological parameters of the stems and conducted physical and mechanical tests. Clone TG3 displayed the largest heartwood diameter, exceeding 15 cm, which was 14% larger than that of clone TG2; the lowest average value was observed for the seminal material. The mean conicity for all materials was 1.84%. In terms of log flattening, all evaluated materials had mean values above 80%. The highest basic density (0.600 g/cm³) was recorded in the wood of clone TG2, surpassing that of clone TG3 by 6.9%, which had the lowest density (0.560 g/cm³). Volumetric shrinkage from clonal materials was greater (8.7%) than that from seminal material (6.58%). The compression parallel to the grain did not significantly vary, with an average value of 47.5 MPa. The second chapter evaluated 13-year-old teak wood from three genetic materials (clones TG1 and TG3 and seminal material) in monocultures located in Nova Maringá and Água Boa, MT. We extracted discs from the base of each tree every 2.3 meters, up to 11.5 meters, to determine the average diameter and heartwood diameter. We used 2.3-meter discs to determine morphological parameters such as percentages of pith, heartwood, sapwood, and bark, as well as pith eccentricity and physical properties. Mechanical tests were conducted using logs taken from the base. Trees from Nova Maringá had the highest percentage of heartwood (56.07%), and clone TG1 had the highest percentage among the materials (54.18%). The TG3 in Água Boa exhibited the highest apparent density (0.618 g/cm³), and there was no difference in density regardless of the material in Nova Maringá. The shrinkage of clonal materials was 15% greater than that of seminal material, and wood from Água Boa was less stable than that from Nova Maringá. For shear strength, the seminal material in Nova Maringá exhibited the highest load (10.42 MPa), along with clone TG3 in Água Boa (10.62 MPa), as did compressive strength and other mechanical tests. Our findings suggest that the characteristics of teak woods from a silvopastoral system are similar to those from monocultures, with clonal materials standing out in comparison to seminal material. The 13-year-old teak woods evaluated in this study exhibited satisfactory properties, indicating their suitability for log trading and lumber production.